THE EFFECT OF SYSTEMIC RISK ON CORPORATE RETURNS - Heydari, Mohammad; Xiaohu, Zhou; Lai, Kin Keung; Yuxi, Zheng (Proceedings of National Aviation University (archive), 2020)
Background: This article seeks to complement the previous literature and clarify the risk of an asset is the probable change in the future return on that asset. In another definition, the asset risk is the difference between the actual return on investment and its expected return. Aim: This article seeks to identify the determinants, to find a significant relationship between systematic risk and return on stocks in the Tehran Stock Exchange (TSE) with a method different from conventional econometric methods. Setting: This article examines the time range of, financial information related to the performance of financial years 2012 to 2017 all companies accepted in Tehran Stock Exchange (TSE) that are producers of chemical and detergent materials that their number is 30. Methods: In order to test the hypothesis of the research, we analyze the information on systemic risk and stock returns of two oscillation and low oscillation periods using a discrete wavelet overlapping (DWT) transformation method with a wavelet with a smaller time period using MATLAB software, then to test the research hypotheses Regression analysis has been used to investigate the movement between them. After collecting the information required by the companies, the research hypotheses were analyzed using wavelet analysis and analyzed using SPSS and MATLAB software. Results: Research hypothesis test results indicate a significant relationship between systematic risk and return in periods of high volatility and long-term vision and long term there. Then to test the hypothesis study, regression analysis is used. Research hypothesis test results indicate a significant relationship between systematic risk and return in periods of high volatility and long-term vision and long term there. Conclusion: The results show that there is a meaningful relationship between systemic risk and returns over a period of fluctuation in the medium to long term horizons. In times of low volatility, there is a significant relationship between systemic risk and return on medium-term horizons (94 and 50 days), but only in the long-run horizon of 182 days is a meaningful relationship between risk and return.